Sales force Attitude toward Market Orientation and impact on Innovative Performance with Mediating Effect of Creativity (Case-study of Iran-Transfo Industrial Group) - Jamshidi & Fereshteh Lotfizadeh, Tahmineh (British Journal of Marketing Studies, 2017)
This study investigated the effect of market orientation of sales force on innovative performance with mediating effect of creativity: case-study of Iran Transfo Industrial Group. Research population included 150 sales force of Iran Transfo Industrial Group from which 108 were selected as sample. Data were collected through questionnaire and survey. Each item was based on 5-points Likert Scale. Face and content validity were used to validate the scale. To examine reliability Cronbach’s Alpha, Split half, and test-retest were employed. SPSS 21 were used to analyze data. In order to test hypothesis, Regression Analysis were used in SPSS data analysis.